ADENINE, ADENOSINE, RIBOSE AND 5′-AMP ADSORPTION TO ALLOPHANE - Hashizume H.; Theng B.K.G. (My University, 2007)
We have investigated the adsorption of adenine, adenosine, ribose, and adenosine-5′-phosphate (5′-AMP) by allophane at pH 4, 6 and 8. Adenine, adenosine and ribose gave similar isotherms, i.e. adsorption increased regularly with solution concentration and decreased in the order: pH 8 > pH 6 > pH 4. Allophane had a greater affinity for 5′-AMP than for adenine, adenosine or ribose. Further, the extent of adsorption for 5′-AMP increased in the order: pH 8 ≪ pH 6 ≈ pH 4. The adsorption of 5′-AMP at pH 4 and pH 6 was about 60 times greater than at pH 8. The strong adsorption of 5′-AMP accords with the well known high phosphate-retention capacity of allophane and allophane-rich soils. The experimental data may be rationalized in terms of the pH-dependent charge characteristics of the organic solutes and allophane. The large propensity of allophane to retain 5′-AMP is ascribed to ligand exchange between the phosphate of 5′-AMP and the hydroxyl of (HO)Al(OH2) groups, exposed at perforations on the wall of allophane spherules, giving rise to a surface (chelation) complex. The high affinity of nucleotides for allophane has implications for the possible role of allophane in the abiotic formation of RNA-type polynucleotides although nucleotide ‘immobilization’ by surface complexation might hinder RNA oligomerization.
Keywords: ADENINE; ADENOSINE; ALLOPHANE; 5′-AMP; ADSORPTION; RIBOSE